Prospects for CARICOM services exports in information and communications technology : trade and investment issues - Cleland, Celene M. (Caribbean Regional Negotiating Machinery BridgetownBB, 2003)
Discusses and assesses the challenges to CARICOM deriving from various negotiating fora and processes for services, in particular as it relates to CARICOM services exports in information and communications technology. Makes recommendations on how CARICOM as a region should approach impending negotiations.